STUDI PERBANDINGAN ENKRIPSI STEGANOGRAFI DENGAN MENGGUNAKAN METODE LEAST SIGNIFICANT BIT DAN END OF FILE - Antonio, Harianto (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
Communications and informationtechnology is rapidly grows and provides amajor influence on people's lives. The rapiddevelopment of information technology iscurrently supported by the importance of theneed for information. It can be seen from the development of today's internet network israpidly increasing. Informations thattransmitted is not meant for everyone. Alongwith the development of these technologies,security threats becomes more and morepowerful, particularly for the undisclosedinformation. Various threats in cyberspace suchas hacker, cracker, carder makes people worryabout the security of the information they sends.This concern that make the development ofinformation hiding techniques. One of the wellknown information hiding technique issteganography. In general, steganographymeans a technique and art of hiding a fact tocommunicate. By using steganography, secretmessage can be inserted into an unsuspiciousinformation and send it without being aware ofthe existence of the secret message. There areseveral criteria that must be considered insteganography is fidelity, robustness, andrecovery. Fidelity means that stegomediumquality has not changed much due to the insertion. The changes can not be perceived bythe senses.